Can multilateralism contribute to solving the climate crisis? - Michael M. Bechtel; Michael R. Cannon (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Michael Cannon and Michael Bechtel explain how despite the history of global climate negotiations being a history of policy failure, multilateral approaches to climate policy could still be an important tool for addressing climate change, war, hunger and poverty, economic meltdowns, and public threats.
Keywords: 330; Klimaschutz; Internationale Zusammenarbeit; Meinung; Welt; Deutschland; Großbritannien; Frankreich; USA